2020
DOI: 10.1136/bmjopen-2019-032204
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery following hip and knee arthroplasty: a systematic review of cost-effectiveness evidence

Abstract: ObjectivesTo assess cost-effectiveness of enhanced recovery pathways following total hip and knee arthroplasties. Secondary objectives were to report on quality of studies and identify research gaps for future work.DesignSystematic review of cost–utility analyses.Data sourcesOvid MEDLINE, Embase, the National Health Service Economic Evaluations Database and EconLit, January 2000 to August 2019.Eligibility criteriaEnglish-language peer-reviewed cost–utility analyses of enhanced recovery pathways, or components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…Findings are in keeping with the results of a recent systematic review in to the cost effectiveness of ER programmes with TKA and THA. 12 On the whole, ER programmes were regarded to be cost-effective, with the AMSTAR tool 8 suggesting moderate confidence in these results. This has justified the programme’s sustainability long term.…”
Section: Resultsmentioning
confidence: 99%
“…Findings are in keeping with the results of a recent systematic review in to the cost effectiveness of ER programmes with TKA and THA. 12 On the whole, ER programmes were regarded to be cost-effective, with the AMSTAR tool 8 suggesting moderate confidence in these results. This has justified the programme’s sustainability long term.…”
Section: Resultsmentioning
confidence: 99%
“…Recent systematic reviews by Zhu et al [ 11 ] and Deng et al [ 12 ] found ERAS programs reduced both LOS and incidence of complications in the 30 days following THA and TKA, without driving a commensurate increase in re-admission following discharge. In addition, one previous review on the cost-effectiveness of ERAS pathways found ERAS surgery to be dominant compared with conventional treatment [ 17 ]. To date, available systematic reviews have yet to explore the evidence relating to other post-acute care outcomes such as emergency department visits, postoperative primary care visits, and revision surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the previously published systematic reviews have not assessed the impact of the number of type of items that may be combined as part of a particular ERAS program. Rather, they have focused only on comparing cohorts undergoing surgery informed by ERAS principles and those without [ 11 , 12 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent systematic reviews by Zhu et al [11] and Deng et al [12] found ERAS programs reduced both LOS and incidence of complications in the 30 days following THA and TKA, without driving a commensurate increase in re-admission following discharge. In addition, one previous review on the cost-effectiveness of ERAS pathways found ERAS surgery to be dominant compared with conventional treatment [17]. To date, available systematic reviews have yet to explore the evidence relating to other post-acute care outcomes such as emergency department visits, postoperative primary care visits, and revision surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the previously published systematic reviews have not assessed the impact of the number of type of items that may be combined as part of a particular ERAS program. Rather, they have focused only on comparing cohorts undergoing surgery informed by ERAS principles and those without [11,12,17].…”
Section: Introductionmentioning
confidence: 99%